The impact of observers’ beliefs on the perceived contribution of a Research Lesson - Caballero, Daniela; Mella-Defranchi, Eliacim; Araya, Roberto (Frontiers in Education, 2024)
Recently, Lesson Study (LS) has gained popularity in countries worldwide because of its potentially positive effects on teachers’ practices (e.g., reflection, cooperation, and pre-service development) and students’ learning. However, despite global interest in LS’s implementation, an important gap exists between Japanese LS and its implementation in other countries, which may be due to several reasons, such as differences in culture and educational systems or teachers’ beliefs. In this study, we examined the effect of teachers’ beliefs on their evaluation of LS in Chile. We administered a questionnaire to 94 teachers who participated in the Research Lesson (RL) as observers. The questionnaire assessed teachers’ beliefs and RL’s contributions to knowledge of the subject matter, instructional strategies, monitoring skills, lesson planning, and student understanding. Using a stepwise logistic regression, after controlling for sex and occupation, we found that the observers’ beliefs influenced their perceptions of RL’s contributions to monitoring, assessment, and instruction. Participants with student-focused beliefs were more likely to find that RL contributed to their monitoring skills and ability to assess students’ understanding of content. The results regarding instructional strategies were mixed. Our findings can help devise strategies to increase the effectiveness of LS implementation. For example, by designing two types of LS, one adapted to teachers with student-focused teaching beliefs and the other to teacher-focused teaching beliefs. To the best of our knowledge, this dual strategy is not part of LS implementation, at least in Chile. LS teams could easily explore this dual strategy, which could improve teachers’ professional development.